2014
DOI: 10.1080/02705060.2014.939108
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dissolved organic carbon in eutrophic Lake Taihu and its tributaries and their implications for bacterial abundance during autumn and winter

Abstract: to investigate the effects of dissolved organic carbon (DOC) dynamics on bacterial abundance. DOC concentrations, stable carbon isotope values (d 13 C DOC ), dissolved carbohydrates, and specific ultraviolet absorbance (SUVA 254 ) were analyzed along with several environmental factors: water temperature, electrical conductivity (EC), chlorophyll a, and bacterial abundance. The highest DOC concentrations were observed in January 2013 at all sampling sites except at lake center. DOC concentrations decreased alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Electrical conductivity (EC) was measured in the Kokosing samples, which has been shown to be an indirect indicator for dissolved organic carbon (DOC) ( 42 44 ). Previous studies have found connections between DOC and ARG abundance ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity (EC) was measured in the Kokosing samples, which has been shown to be an indirect indicator for dissolved organic carbon (DOC) ( 42 44 ). Previous studies have found connections between DOC and ARG abundance ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…2005; Ye et al . 2015). Because methane produced in the sediments accumulate in high amounts in the lower parts of the water column (Houser et al .…”
Section: Introductionmentioning
confidence: 99%
“…This shows high level of organic carbon (DOC) in the rivers. EC is an indirect indicator of DOC 25 , 50 , 51 and found to have associations with Acinetobacter -specific ARG and other ARG abundance 25 , 52 , 53 . Generally, A. baumannii in the environment can survive irrespective of the level of DO 54 .…”
Section: Discussionmentioning
confidence: 99%